The Talking Stick Learning Model in Geography Lessons at Sma Negeri 17 Pekanbaru, Indonesia - bin Radin Abdul Halim, Radin Muhd. Imaduddin; bin Ismail, Ahmad Munsif; Dedi Iswara; Budi Handoyo (Sumatra Journal of Disaster, Geography and Geography Education, 2026)
The purpose of this research is to analyze the improvement of learning activity results and learning outcomes through the Talking Stick learning model. This type of research is classroom action research which is carried out through the stages of planning, implementation, observation, and reflection. This research looks at student learning activities including visual activities, oral activities, mental activities, listening activities, writing activities, and emotional activities. The data collection tool used is a worksheet. observation of student learning activities and learning outcome tests. The results of the study show that (1) Learning activities observed from the learning process using the talking stick learning model increased from cycle I to cycle II. The average active student learning activity in cycle I was 44.87% and increased to 79.3% in cycle II. (2) The learning outcome value from the Daily Assessment (PH) conducted at the 4th meeting of each cycle also increased the number of students who achieved KKM ≥85, namely 52.7% completed cycle I and in cycle II increased to 86.11%. So it can be concluded that geography learning using the talking stick learning model can improve students' learning activities and learning outcomes in the biodiversity material for grades XI-4